Dissecting the Idea of Ethics Education in the Book of Akhlaqul Banin: A Reflective-Critical Study - Mochammad Nur Hadi; M. Yunus Abu Bakar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to examine and understand the concept of ethics and moral education in the book of Akhlaqul Banin by Shaykh Umar bin Ahmad Baraja. This book is known as a guide that presents moral values that must be applied in everyday life, especially for children. In this research, a critical study approach was used by the researcher to explore the thoughts of Shaykh Umar bin Ahmad Baraja with ethical education, as well as the relevance of moral teachings in the book to the context of moral education today. The conclusion of the research shows that the book of Akhlaqul Banin strongly emphasises the importance of instilling moral and ethical values from an early age. The ethical education taught in this book focuses on the formation of good character through religious teachings, with the aim of producing individuals who have noble character, politeness, and social responsibility. Although the book was written in a traditional context, the thoughts of Shaykh Umar bin Ahmad Baraja are still relevant to be applied in modern education today, especially in responding to the moral challenges faced by today's young generation. This research also raises the concepts contained in the book of Akhlaqul Banin, which will then be used as guidelines in the development of moral education curriculum at all levels of education, from primary to secondary levels. By looking for the value of education in this book, it is hoped that the author will be able to find a concise way to form a generation that is not only intelligent, but also noble and responsible in facing the increasingly complex challenges of the world in the future.